PERFORMANCE AGRICULTURAL, MINING, AND INDUSTRIAL SECTORS IN SOUTH SUMATRA PROVINCE BEFORE AND DURING THE COVID-19 PANDEMIC - Muhammad Aris Pujiyanto; Dwidjono Hadi Darwanto; Jangkung Handoyo Mulyo (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2025)
Now, COVID-19 pandemic which began in Wuhan, China, on December 2019, has been affecting several lethal health problems that ever happened throughout global history. Without exception for Indonesia which was confirmed that COVID-19 has been occurring since 2 March 2020. COVID-19 pandemic has been affecting many sectors including agricultural, mining, and industry. This research aims to understand the impact of COVID-19 pandemic on changes in Gross Regional Domestic Product (GDRP), growth, contribution, and base sectors in agriculture, mining, and industry. This study used secondary data. This study used multiple linear regression analysis with dummy variables and Location Quotient (LQ) analysis. The results showed agricultural sector had no changes in GDRP either positive or negative; mining sector had negative changes in GDRP, while industrial sector had positive changes in GDRP. Agricultural, mining, and industrial sectors had no growth changes either positive or negative. Only the mining sector had decreased in contribution during COVID-19 pandemic. Only the industrial sector is a non-basic sector, while the agriculture and mining sectors are the basic sector, but experienced a decline in LQ values during the COVID-19 pandemic.